2001
DOI: 10.1016/s0896-6273(01)00464-0
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of IP3 Dynamics Reveals a Novel AMPA Receptor-Triggered IP3 Production Pathway Mediated by Voltage-Dependent Ca2+ Influx in Purkinje Cells

Abstract: IP(3) signaling in Purkinje cells is involved in the regulation of cell functions including LTD. We have used a GFP-tagged pleckstrin homology domain to visualize IP(3) dynamics in Purkinje cells. Surprisingly, IP(3) production was observed in response not only to mGluR activation, but also to AMPA receptor activation in Purkinje cells in culture. AMPA-induced IP(3) production was mediated by depolarization-induced Ca(2+) influx because it was mimicked by depolarization and was blocked by inhibition of the P-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 74 publications
5
79
2
Order By: Relevance
“…We therefore tested whether the increase in [Ca 2ϩ ] i could directly stimulate PLC activation and DAG production in these neurons. Evidence for such a direct mechanism has been obtained in biochemical and cellular studies in insulin-producing cells, glial cells, and cerebellar neurons (Mizuguchi et al, 1991;Rebecchi and Pentyala, 2000;Codazzi et al 2001;Okubo et al, 2001;Mogami et al, 2003). We now report that Ca 2ϩ activation of the ␦ isoform of PLC is likely responsible for this response.…”
Section: Maximal Activation Of Iglurs Is Sufficient To Promote Dag Prsupporting
confidence: 50%
“…We therefore tested whether the increase in [Ca 2ϩ ] i could directly stimulate PLC activation and DAG production in these neurons. Evidence for such a direct mechanism has been obtained in biochemical and cellular studies in insulin-producing cells, glial cells, and cerebellar neurons (Mizuguchi et al, 1991;Rebecchi and Pentyala, 2000;Codazzi et al 2001;Okubo et al, 2001;Mogami et al, 2003). We now report that Ca 2ϩ activation of the ␦ isoform of PLC is likely responsible for this response.…”
Section: Maximal Activation Of Iglurs Is Sufficient To Promote Dag Prsupporting
confidence: 50%
“…However, recent results showed that both AMPAR and mGluR collaborate in the generation of the Ca 2ϩ signal and EPSC at PF3 Purkinje cell synapses (Eilers et al, 1995;Finch and Augustine, 1998;Takechi et al, 1998;Tempia et al, 1998;Kim et al, 2003). On the other hand, our recent finding that the activation of AMPAR induces IP 3 production through Ca 2ϩ influx in Purkinje cells (Okubo et al, 2001) raised the possibility that not only mGluR but also AMPAR participates in the generation of an IP 3 signal at PF3 Purkinje cell synapses. However, this possibility has not been tested at the synaptic sites because of the lack of technique to measure IP 3 dynamics with a sufficient spatiotemporal resolution.…”
Section: Introductionmentioning
confidence: 87%
“…Twenty-four hours after transfection, the culture medium was harvested because this contained the infectious particles of Sindbis virus (SIN)-IRES-GFP-PHD. IRES-dependent translations were shown to be less efficient than capdependent translations (Ehrengruber et al, 1999;Okubo et al, 2001) and were used here to avoid the overexpression of GFP-PHD. Rat IP 3 5-phosphatase (Hirose et al, 1999) was cloned into pSinRep5 with IRES-GFP-PHD to generate the cDNA encoding 5-phosphatase [wild type (WT)]-IRES-GFP-PHD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This probe binds PIP 2 with high specificity and affinity (20) but translocates to the cytoplasm when IP 3 accumulates (and PIP 2 depletes) (16,(21)(22)(23). We have transfected this probe into cultures of rat hippocampal neurons and show a dramatic facilitation of IP 3 production, which promotes Ca 2ϩ store release.…”
Section: Intracellular Camentioning
confidence: 99%